What Controls the Magnitude and the Shape of Landslide Dam-Breaching Flood Hydrograph? Case Studies of Emergent Forecasts for Outburst Floods of Jiala and Baige Barrier Lakes - Song, Yuntian; Fu, Xudong; Lin, Yongpeng; An, Chenge; Ma, Hongbo (Frontiers in Water, 2022)
Outburst floods released by failing barrier dams are likely to be catastrophic, posing high risk to downstream area. However, emergent forecast of the breaching process is still a challenging work due to the complex mechanisms as well as the lack of adequate data. During October and November in 2018, four tremendous barrier lakes formed on the Jinsha River and the Yarlung Zangbo River, China. In the course of the emergency treatment of the breach of landslide dams, the parameters for simulation were obtained in relatively short time based on the information from aerial images, DEM data and hydrological measurement. A physically-based dam-breach model was established in this paper and has been successfully implemented in the prediction of the breaching processes of the “October 17” and “October 29” Jiala barrier dams on the Yarlung Zangbo River, providing the pivotal information to support the decision-making of the hazard mitigation. With refined dam height and grain size distribution, the model can also well reproduce the breaching process of “November 3” Baige barrier dam on the Jinsha River. Both field data and our numerical simulation showed that the magnitude and the shape of the landslide dam-breaching flood hydrograph were affected by the dam morphology as well as the composition of dam material. Two patterns of outburst flood hydrographs of landslide dams with distinct symmetries were identified based on the statistical analysis of the available data. The approximately symmetrical breach hydrograph of the “November 3” Baige barrier lake could be partly attributed to the relatively fine grain size distribution of its dam material.